The identification of viral ribonucleotide reductase encoded by ORF23 and ORF141 genes and effect on CyHV-2 replication - Cheng, Wenjie; Chen, Qikang; Ren, Yilin; Zhang, Ye; Lu, Liqun; Gui, Lang; Xu, Dan (Frontiers in Microbiology, 2023)
Introduction Ribonucleotide reductase (RR) is essential for the replication of the double-stranded DNA virus CyHV-2 due to its ability to catalyze the conversion of ribonucleotides to deoxyribonucleotides, and is a potential target for the development of antiviral drugs to control CyHV-2 infection. Methods Bioinformatic analysis was conducted to identify potential homologues of RR in CyHV-2. The transcription and translation levels of ORF23 and ORF141, which showed high homology to RR, were measured during CyHV-2 replication in GICF. Co-localization experiments and immunoprecipitation were performed to investigate the interaction between ORF23 and ORF141. siRNA interference experiments were conducted to evaluate the effect of silencing ORF23 and ORF141 on CyHV-2 replication. The inhibitory effect of hydroxyurea, a nucleotide reductase inhibitor, on CyHV-2 replication in GICF cells and RR enzymatic activity in vitro was also evaluated. Results ORF23 and ORF141 were identified as potential viral ribonucleotide reductase homologues in CyHV-2, and their transcription and translation levels increased with CyHV-2 replication. Co-localization experiments and immunoprecipitation suggested an interaction between the two proteins. Simultaneous silencing of ORF23 and ORF141 effectively inhibited the replication of CyHV-2. Additionally, hydroxyurea inhibited the replication of CyHV-2 in GICF cells and the in vitro enzymatic activity of RR. Conclusion These results suggest that the CyHV-2 proteins ORF23 and ORF141 function as viral ribonucleotide reductase and their function makes an effect to CyHV-2 replication. Targeting ribonucleotide reductase could be a crucial strategy for developing new antiviral drugs against CyHV-2 and other herpesviruses.